The trouts of the Marmara and Aegean Sea drainages in Türkiye, with the description of a new species (Teleostei, Salmonidae) - Davut Turan; Esra Bayçelebi; Sadi Aksu; Münevver Oral (Zoosystematics and Evolution, 2024)
The taxonomic status of native trout species of the Marmara and Aegean Sea drainages is evaluated and three species, Salmo duhani, S. coruhensis and S. brunoi sp. nov., are recognized. Salmo brunoi, a new species, is described from the Nilüfer River, a tributary of the Susurluk River. It is distinguished by a general brownish body color in life; few black spots (fewer than 60) on the body, generally scattered on the back and the upper part of the flank, rarely in the median part; few (fewer than 40) and small (smaller than pupil) red spots on the body, scattered on the median part and lower half of the flank; a number of black and red spots not increasing with size in both sexes; a long adipose fin (adipose-fin height 8–9% SL); a short distance between adipose-fin and caudal-fin (12–14% SL); and a short anal fin (anal-fin height 12–15% SL). Salmo brunoi sp. nov. is separated from the rest of the Marmara and Aegean trouts of Anatolia based on genome-wide distributed 187.385 unlinked SNP markers. According to the best of the authors’ knowledge, whole genome data is used for the first time here to characterize a new species of trout.